A Mixed-Methods Study of Former Child Soldiers' Transition Trajectories From Military to Civilian Life. (May 2017) - Vindevogel, Sofie; Van Parys, Hanna; De Schryver, Maarten; Broekaert, Eric; Derluyn, Ilse
Child soldiering affects the well-being of thousands of young people globally and inflicts significant challenges on entire socio-ecological systems, confronting them with culminating stressful living conditions and immense loss. This study sought to explore how former child soldiers' transition trajectories are shaped by the dynamic interplay between these encountered challenges and available personal and communal resources. We conducted and analyzed in-depth interviews with 48 northern Ugandan former child soldiers using cluster analysis ( K -means) and interpretative-phenomenological analysis. The results showed divergent post-child soldiering trajectories of stability, improvement, or decline across time. Regarding resources, the cases showed ongoing resource depletion, threat to remaining resources in the face of significant challenge, and loss of resources that could not be replenished. However, there was also evidence that halting the depletion of resources, utilizing existing resources, and valuing remaining resources could offset distress, especially when individual initiatives were environmentally scaffolded. This study calls for a comprehensive approach to the interconnected challenges and resources as well as the intersecting personal and communal responses to these challenges in the aftermath of child soldiering.